EFFECT OF VARYING VOLTAGE ON ELECTRON DENSITY IN OXYGEN HOMOGENEOUS DIELECTRIC BARRIER DISCHARGE UNDER ATMOSPHERIC PRESSURE - Khan, Ali Akbar; Ling, Yap Seong; Chowdhury, Zaira Zaman (Malaysian Journal of Science, 2019)
The formation of uniform dielectric barrier discharges (DBDs) under atmospheric pressure is a remarkable achievement with the addition of electronegative gasses in closed reactors. This work is the part of dielectric barrier discharge achieved under atmospheric pressure. A uniform glow discharge is produced in capacitive discharge reactor. An alternating voltage source (0-2.5) kV having frequency of 50Hz is applied across the two parallel disc electrodes. A couple of dielectrics (glass) used as a discharge barriers one on each electrode. The oxygen gas injected into the reactor controlled by mass flow controller with flow rate 30ml/min. The current-voltage waveforms for oxygen discharge achieved, fulfilling the basic conditions of discharge homogeneity. The diagnostic techniques rely on electrical discharge method and power balance method to differentiate discharges and estimate the electron density for different values of applied voltages. A significant relation is found indicating the variation of electron density with applied voltage.